ANATOMI DELAPAN JENIS KAYU KURANG DIKENAL DARI SUKU FLACOURTIACEAE SAMPAI JUGLANDACEAE (Wood anatomy of eight lesser known wood species of Flacouriiaceae to Juglandaceae) - Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Gross and anatomical features of eight lesser known wood species belongs to 5 families from Flacourtiaceae to Juglandaceae were observed and described for identification purposes. Fiber dimension were also measured for evaluation of their suitability for pulp. Septate fibers, vessels in radial multiples. some ray longitudinallyfused are the main characters of Homalium and Trichadenia (Flacourtiaceae). Bucklandia and Distylium (Hamamelidaceae) are characterized by small and polygonal vessel, scalariform perforation plate, and disjunctive end wall at upright ray cells. Urandra and Platea (Icacinaceae) are characterized by two type of ray width, fibers with distinctly bordered pit, scalariform perforation plate.and yellowish wood colour. Four species contain fibers with medium quality for pulp (Engelhardtia spicata, Bucklandia triscuspis, Platea latifolia, and Trichadenia philippinensis). The rest four species contain fibers with poor quality. Trichadenia philippinensis is the only one among eight wood species examined which has decorative appearance : moderatelyfine texture, bright yellow in colour and considerable high density. It is thereforepossible to be used as